2019
DOI: 10.3389/fncel.2019.00296
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Conformations, Aggregation and Cellular Internalization of Different Tau Strains

Abstract: The inter-cellular propagation of tau aggregates in several neurodegenerative diseases involves, in part, recurring cycles of extracellular tau uptake, initiation of endogenous tau aggregation, and extracellular release of at least part of this protein complex. However, human brain tau extracts from diverse tauopathies exhibit variant or “strain” specificity in inducing inter-cellular propagation in both cell and animal models. It is unclear if these distinctive properties are affected by disease-specific diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 82 publications
(157 reference statements)
1
37
0
Order By: Relevance
“…To exclude the possibility that tau-K18 C291R's aggregation into non-fibrillar structures was dependent on heparin induction, the experiment was repeated in native-state conditions by incubating both tau constructs in identical conditions as in Figure 3 except that no heparin was added. Aggregation was slower in this condition as anticipated (Karikari et al, 2019a). However, this approach allowed the fine mechanistic details of the process to be studied.…”
Section: Tau-k18 C291r Aggregates Into Non-fibrillar Amorphous and Anmentioning
confidence: 60%
See 2 more Smart Citations
“…To exclude the possibility that tau-K18 C291R's aggregation into non-fibrillar structures was dependent on heparin induction, the experiment was repeated in native-state conditions by incubating both tau constructs in identical conditions as in Figure 3 except that no heparin was added. Aggregation was slower in this condition as anticipated (Karikari et al, 2019a). However, this approach allowed the fine mechanistic details of the process to be studied.…”
Section: Tau-k18 C291r Aggregates Into Non-fibrillar Amorphous and Anmentioning
confidence: 60%
“…We generated the pProEx-HTa-Myc-6 × His-K18 plasmid carrying the C291R mutation (TGT > CGT, the same codon change previously reported by Marshall et al, 2015) by site-directed mutagenesis using a WT tau-K18 plasmid as a template (Karikari et al, 2017(Karikari et al, , 2019a. Protein expression and purification were achieved using our previously-characterized recombinant tau production protocols (Karikari et al, 2017(Karikari et al, , 2019aHill et al, 2019). The purified His-tagged tau-K18 constructs were used directly in functional experiments since the His-tag does not appear to affect aggregation (Huseby et al, 2019).…”
Section: Cloning Protein Expression and Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we assessed whether blocking endocytosis would alter aggregation, possibly by reducing the seeding step of protein aggregation 8, 62 . Dynamins play essential roles in membrane remodeling and fission of clathrin-coated vesicles formed during endocytosis 63,64 .…”
Section: Discussionmentioning
confidence: 99%
“…Although polyQ diseases are well known clinically, their molecular mechanism and cell biological behavior are still unclear, especially in the context of PME. To address this issue, in the present study, a wild-type (wt) human Cav2.1 (Cav2.1 wt) with 13 repeats of CAG as well as a mutant-type (mt) Cav2.1 (Cav2.1 mt) with 26 repeats of CAG in the C-terminus of this protein were constructed and delivered into cells of the SH-SY5Y neuroblastoma cell line, which is always used as the model cell line for investigations of human nervous system diseases (10)(11)(12). The results revealed that the forced expression of Cav2.1 mt significantly inhibited SH-SY5Y cell proliferation by inducing apoptosis.…”
Section: Introductionmentioning
confidence: 99%